2016
DOI: 10.21809/rilemtechlett.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Overview on cold cement bitumen emulsion asphalt

Abstract: Cold mix asphalt, a promising substitute for conventional hot mix asphalt, is manufactured at ambient temperature using bitumen emulsion as binder. To improve its strength and durability, cement is often added to the mixture. This review (1) presents an overview about advances in cold mix asphalt modified with cementitious materials, often called CBEA (cement bitumen emulsion asphalt), (2) illustrates advantages and disadvantages of CBEA and (3) gives recommendations to produce homogenous CBEA mixtures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Moreover, Figure 9(b) shows the influence of the addition of 1% Portland cement on the Marshall force resisted, measured at different curing times in CMA and CMC materials. In it can be observed that cement addition improved the strength of all the materials studied, which is consistent with results found by Fang et al (2016), where the cement to increase the strength of CMA specimens.…”
Section: Effect Of Binder Type and Amount On The Mechanical Strength Of Cold Mixes At Different Curing Timessupporting
confidence: 90%
“…Moreover, Figure 9(b) shows the influence of the addition of 1% Portland cement on the Marshall force resisted, measured at different curing times in CMA and CMC materials. In it can be observed that cement addition improved the strength of all the materials studied, which is consistent with results found by Fang et al (2016), where the cement to increase the strength of CMA specimens.…”
Section: Effect Of Binder Type and Amount On The Mechanical Strength Of Cold Mixes At Different Curing Timessupporting
confidence: 90%
“…Nowadays, environmental and economical requirements are pushing the development of eco-friendly and low-energy road paving materials. In this regard, bitumen emulsion mixtures play an important role because they are manufactured at ambient temperature and therefore, significantly reduce carbon dioxide emissions and energy consumption, with respect to hot and warm bituminous mixtures [1,2]. Bitumen emulsion mixtures are also widely used in cold recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CBE mastic could show low fatigue and fracture resistance under high load cycles [ 17 ]. Therefore, the mechanism of filler reinforcement in CBE mastic plays a major role in controlling the distress and failure mechanisms in the CBE mixture [ 18 ]. During its service life, the CBE mixture is subjected to different distress.…”
Section: Introductionmentioning
confidence: 99%